Implementation of Pharmaceutical Care to Improve Therapeutic Outcomes and Quality of Life in Type 2 Diabetes Mellitus Patients at Batubara Public Health Center - Citra Syahriani Damanik; Khairunnisa Khairunnisa; Wiryanto Wiryanto (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2026)
Background: Pharmacists have a significant function in delivering pharmaceutical care services aimed at maximizing therapeutic success for individuals with type 2 diabetes mellitus. Objective: The objective of this research was to evaluate the impact of pharmaceutical care practices on medication adherence, therapeutic outcomes, quality of life, and the frequency of drug-related problems (DRPs) in patients diagnosed with type 2 diabetes mellitus at Batubara community health centers. Methods: This research employed a comparative experimental approach with a prospective cohort design, assessing 66 participants across three community health centers during a three-month period before and after the intervention. Medication adherence was measured using the MARS-5 questionnaire, while DRPs were identified with the PCNE V9.1 instrument. Therapeutic outcomes were determined from random blood glucose (RBG) and HbA1c levels, and the Diabetes Quality of Life Clinical Trial Questionnaire (DQLCTQ) was used to assess quality of life. Data analysis was conducted using the Wilcoxon Signed Rank Test and Friedman Test via SPSS version 22.0. Results: The mean medication adherence score improved substantially from 5.21±0.90 to 23.39±1.78 following pharmaceutical care intervention. The average number of DRPs per patient declined from 1.26±0.44 to 0.12±0.48. Moreover, mean RBG levels decreased from 305.79±82.86 mg/dl to 194.62±67.67 mg/dl, and HbA1c levels reduced from 9.37±1.52% to 8.69±1.48%. The mean quality of life score also showed an increase from 7.20±0.90 to 11.14±0.77. Conclusion: The provision of structured pharmaceutical care significantly improved medication adherence, optimized therapeutic outcomes, minimized drug-related problems, and enhanced the overall quality of life of type 2 DM patients in Batubara community health centers.